Zuo-Gui-Wan Aqueous Extract Ameliorates Glucocorticoid-Induced Spinal Osteoporosis of Rats by Regulating let-7f and Autophagy - Shen, Gengyang; Shang, Qi; Zhang, Zhida; Zhao, Wenhua; Chen, Honglin; Mijiti, Ibrayinjan; Chen, Guifeng; Yu, Xiang; Yu, Fuyong; Zhang, Peng; He, Jiahui; Zhang, Xuelai; et al. (Frontiers in Endocrinology, 2022)
Objective: This study proposes to explore the protective effect of Zuo-Gui-Wan (ZGW) aqueous extract on spinal glucocorticoid-induced osteoporosis (GIOP) in vivo and in vitro, and the underlying mechanisms of ZGW in GIOP and osteogenic differentiation of bone marrow derived mesenchymal stem cells (BMSCs) were conducted. Methods: In vivo, SD rats were randomly divided into three groups: Control group (CON), dexamethasone (DEXM) and ZGW group, which were given vehicle, DEXM injection and ZGW intragastric administration at the same time. Vertebral bone microarchitecture, biomechanics, histomorphology, serum AKP activity, and the autophagosome of osteoblasts were examined. mRNA expressions of let-7f, autophagy-associated genes (mTORC1, Beclin-1, ATG12, ATG5, and LC3), Runx2, and CTSK were examined. In vitro, the let-7f overexpression/silencing vector was constructed and transfected to evaluate the osteogenic differentiation of BMSCs. Western blot was employed to detect the expression of autophagy-associated proteins (ULK2, ATG5, ATG12, Beclin-1, LC3). Results: In vivo, ZGW promoted bone quantity and quality, bone strength; alleviated histological damage; increased serum AKP activity; reduced autophagosome number in osteoblasts. Moreover, ZGW increased let-7f, mTORC1, and Runx2 mRNA expressions, reduced Beclin-1, ATG12, ATG5, LC3, and CTSK mRNA expressions. In vitro, bioinformatics prediction and dual luciferase reporter gene assay verified that let-7f targeted binding to ULK2 and negatively regulated ULK2 expression. Furthermore, by let-7f overexpression/silencing, ZGW may promote osteoblast differentiation of BMSCs by regulating let-7f and autophagy as evidenced by western blot (ULK2, ATG5, ATG12, Beclin-1, LC3). Conclusions: ZGW may ameliorate GC-induced spinal osteoporosis by promoting osteoblast differentiation of BMSCs by activation of let-7f and suppression of autophagy.